Hidradenitis Suppurativa and Ocular Diseases: Real-world Evidence of 57,972 Patients - Jennifer von Stebut-Marx; Robert Preissner; Sylke Schneider-Burrus; Saskia Preissner (Acta Dermato-Venereologica)
Hidradenitis suppurativa (HS) is a chronic inflammatory skin disease characterized by recurring dermal abscesses and cutaneous fistulas of intertriginous skin regions, significantly impacting patients’ quality of life. While HS has been associated with various comorbidities such as metabolic and chronic inflammatory diseases, many systemic effects of this systemic disease remain to be investigated. In this study, 2 cohorts of patients with and without HS were created – matched for sex, age, and nicotine dependence – each comprising 28,986 patients, using the real-world database TriNetX, to investigate the association of ocular diseases and HS. Not only an increased risk of disorders of refraction and accommodation in HS patients (OR 3.466; 95% CI 3.100, 3.876), but also a higher risk of ocular diseases, including disorders of the lacrimal system, was demonstrated when compared with the control cohort (OR 3.523; 95%CI 2.912, 4.263). Although previous studies have suggested an increased risk of ocular comorbidities in HS patients, ocular history is not routinely queried during visits. Here, the need for further exploration of the association of ocular diseases and HS and for incorporating this into clinical practice is emphasized.